Effect of continuous positive airway pressure in patients with true refractory hypertension and sleep apnea: a post-hoc intention-to-treat analysis of the HIPARCO randomized clinical trial. Issue 6 (June 2019) - Navarro-Soriano, Cristina; Martínez-García, Miguel-Angel; Torres, Gerard; Barbé, Ferrán; Caballero-Eraso, Candela; Lloberes, Patricia; Diaz Cambriles, Trinidad; Somoza, María; Masa, Juan F.; González, Mónica; Mañas, Eva; de la Peña, Mónica; et al.
Abstract : Rationale: Continuous positive airway pressure (CPAP) can significantly reduce blood pressure (BP) levels in patients with resistant hypertension and sleep apnea (OSA); however, the effect on patients with refractory hypertension (RfH) is not known. This study seeks to evaluate the effect of CPAP treatment on BP levels in patients with OSA and RfH, compared with those with OSA and resistant hypertension. Methods: Post-hoc analysis of the HIPARCO randomized clinical trial on the effect of CPAP treatment on BP levels in patients with resistant hypertension. Those patients with uncontrolled 24-h ambulatory BP monitoring readings (>130 and/or >80 mmHg) in SBP or DBP were considered to have resistant hypertension (if they were taking three or four antihypertensive drugs) or RfH (if they were taking at least five drugs). OSA patients were randomized to receive CPAP or usual care for 3 months. They underwent a second 24-h ambulatory BP monitoring study to establish the effect of CPAP treatment on BP levels in both groups. Results: A total of 98 patients were randomized to CPAP (19 RfH/79 resistant hypertension) and 96 to usual care (21 RfH/75 resistant hypertension). BP readings dropped more marked in patients with RfH than resistant hypertension, in both 24-h SBP (−9 vs. −1.6 mmHg, P  = 0.021) and 24-h DBP (−7.3 vs. −2.3 mmHg, P  = 0.074), especially at night (−11.3 vs. −3.8, P  = 0.121 and −8.8 vs. −2.2, P  = 0.054) respectively. Adjusted difference between groups was statistically significant in 24-h SBP levels (−7.4 mmHg, P  = 0.021). Conclusion: CPAP lowers BP levels in both resistant hypertension and RfH patients although the degree of this reduction is higher in those with RfH especially during the night.